Thermal enhancement in a microchannel heat sink using passive methods / Navin Raja Kuppusamy - Navin Raja , Kuppusamy (2016)
The present work focuses on enhancing the thermal performance of the microchannel heat sink (MCHS) using the passive method. Computational domain of the single channel was selected from the physical model of the MCHS for the numerical simulation. The basic geometry of the computational domain was taken from the geometry of the MCHS from existing literatures. This model was validated with the available analytical correlation and existing numerical results. Five types of passive enhancements were studied in this study. Those methods are; (1) secondary channel, (2) micromixer, (3) constrictions, (4) re-entrant obstruction and (5) cavities. The fluid flow and heat transfer characteristics of all these MCHS were numerically investigated in a laminar and steady state condition at a constant heat flux. The effect of the geometrical parameter on the thermal and pressure loss was studied at different flow configurations. The results showed that passive enhancements of the MCHS significantly improved compared to the simple MCHS. There were a few highlights that were also gathered from this study. Firstly, the performance of secondary flow and micromixer is immensely good where heat transfer increased up to 1.43 times compare to simple MCHS. Furthermore, the pressure drop associated with this enhancement was in fact lower than the simple MCHS (0.97 times that of simple MCHS). Secondly, although constrictions and the re-entrant obstruction improved the performance of the MHCS by 2.25 and 1.2 respectively, the pressure loss associated with this enhancement was substantially high. Finally, the convection heat transfer in the MCHS with cavities improved considerably up to 1.63 with a negligible pressure drop. It was also found that the performance of the MCHS was greatly dependent on the geometrical parameters of passive enhancement except for the constrictions and reentrant obstructions. Such improvement attributes to the increase of the heat transfer area and the repetitive development of the boundary layers. Besides that, the passive enhancement also enhanced the fluid mixing. For instance, the large and intense vortices observed in the cavities, the micromixers and secondary channels resulted in chaotic advection that ultimately improved the convection heat transfer. Similarly, the Eddy effect in the MCHS with constriction also improved the heat transfer. The jet and throttling effect, as well as the fluid acceleration that the fluid experienced after passing the modified section also contributed to the enhancement of heat transfer with some pressure drop penalty. The overall result of the present work shows that the MCHS with passive enhancement has a high potential and is feasible to be implemented in practical applications.